English Online Learning amidst the Pandemic: An Analysis of Vocational Teachers' Performance - Maharrani, Dwi; Pitaloka, Nova Lingga; Amrullah (Indonesian Research Journal in Education |IRJE|, 2023)
In today’s world where technology is inevitable, teachers are expected to adapt to dynamic changes, which requires the integration of technology into classroom activities. However, COVID-19 outbreaks, which forced a sudden shift in the educational system from offline to online learning, pose challenges for teachers. In this study, we examine the performance of vocational English teachers in the Ogan Ilir district, South Sumatera from the perspective of the teachers' self-assessments using qualitative descriptive analysis. Three English teachers from three vocational schools took a teachers' self-assessment questionnaire consisting of forty performance indicators categorized into six performance standards: learning preparation, learning activities, learning evaluation, interpersonal relationships, professional development, and school development. The results revealed that out of four levels, the performance level of the teachers was at level two for the five last standards and level three for the first standard. To better understand their performance, a semi-structured in-depth interview was conducted.